Evaluation and control of the orientation of small molecules for strongly absorbing organic thin films - Schünemann, C; Wynands, D; Eichhorn, K; Stamm, M; Leo, K; Riede, M (American Chemical Society, 2013)
In the photoactive film of organic solar cells, the orientation of the absorber molecules is one of the key parameters to achieve high absorption and high photocurrents as well as efficient exciton and charge transport. However, most organic absorber small molecules, such as zinc-phthalocyanine (ZnPc) or diindenoperylene (DIP) grow more or less upright standing in crystalline thin films. Considering absorption, this molecular alignment is unfavorable. In this work we control the orientation of ZnPc and DIP in crystalline absorber films by varying the substrate or organic underlayer appropriately. For this purpose, a precise evaluation of the molecular orientation and packing is important. We find that a combination of the methods variable angle spectroscopic ellipsometry (VASE) and grazing incidence X-ray diffraction (GIXRD) can fulfill this requirement. The combination of these complementary methods shows that the growth of DIP and ZnPc is nearly upright standing on weakly interacting substrates, like glass or amorphous charge transport films. In contrast, on strongly interacting metal sublayers and PTCDA templating layers, both molecules arrange in a strongly tilted orientation (mean tilt angle 54°-71° with respect to the substrate normal), inducing a significant enhancement of absorption (maximum extinction coefficient from 0.72 to 1.3 for ZnPc and 0.14 to 0.4 for DIP). However, even when deposited on metal or PTCDA sublayers, not all ZnPc and DIP molecules in the film are oriented in the desired flat-lying fashion. This highlights that classifying organic films into either solely flat lying structures or solely upright standing structures, as often made in literature, is a too simplified picture. © 2013 American Chemical Society.